Agile methods : 8th Brazilian Workshop, WBMA 2017, Belém, Brazil, September 13-14, 2017, Revised selected papers /: 8th Brazilian Workshop, WBMA 2017, Belém, Brazil, September 13-14, 2017, Revised selected papers. (2018) - Unknown
No abstract available